Report of the Conference on Disarmament: 2015 Session - United Nations Department for General Assembly; Conference Management (United Nations, 2016)
The Conference on Disarmament submits to the Seventieth session of the United Nations General Assembly its annual report on its 2015 session, together with the pertinent documents and records.